Efficacy of Capacitive Deionization Flow Cell Fabricated with Carbon Nanomaterial Modified Electrodes (Dhaka University Journal of Science, 2024)
The supply of freshwater is becoming a serious global challenge. Capacitive deionization (CDI) has been recognized as apromising and smart desalination technique to solve it. Carbonaceous materials, due to their non-toxic characteristics, areused for filtration, adsorption, and water deionization. In this study, a newly designed, homemade low CDI system wasfabricated, and carbon as electrode material was prepared from waste leather through a one-step activated pyrolysis process. Carbonaceous materials prepared at different temperatures were characterized by Fourier-transform infrared (FTIR), scanning electron microscopy (SEM), and X-ray diffraction (XRD) techniques. The charge storage capacity of the carbon materials casted on a glassy carbon electrode was evaluated using cyclic voltammetric and galvanostatic chargingdischarging techniques. The fabricated CDI system could be successfully used for the study of the removal capacity of NaCl from an aqueous solution. The removal capacity of carbon prepared at 600 °C from leather is 11.58 mgg1, which is about three times higher than commercial activated carbon at flow rate and applied potential of 23 mL min–1 and 1.0 V, respectively.Dhaka Univ. J. Sci. 72(2): 52-60, 2024 (July)